The Spread of Islam in the Niger and Senegal Valleys before the Rise of Almoravids - Hussein, Ahmed Elyas (Intellectual Discourse, 2013)
This study traces the early contacts of the middle and upper Niger and Senegal Rivers with the Muslims in the first five centuries after hijrah and shows the spread of Islam and the rise of states long before the emergence of Al-Moravids. It analyses the early Muslim expansion in the Western Sahara, the role of the Ibāḍiyyah in central Sahara and the efforts of the Sanhadja in the Western Sahara which resulted in the spread of Islam and rise of Islamic kingdoms in the Niger and the Senegal Valleys before the 5th centaury AH.